High-efficiency anomalous reflection of acoustic waves with a passive-lossless metasurface. (25th March 2019) - Zhu, Xing-Feng; Wu, Da-Jian; Lau, Siu-Kit; Liu, Xiao-Jun
Abstract: We present the theoretical, numerical and experimental investigations on the high-efficiency anomalous reflection by a passive-lossless acoustic metasurface (AM). In contrast to the conventional AM, the direction of the reflected waves is controlled by the nonlinear local phase shifts in the passive-lossless AM rather than by the linear modulation. Closed-end tubes are designed to realize the passive-lossless AM. A considerable improvement of 31% in the overall efficiency is confirmed in the passive-lossless AM compared to that based on generalized reflection law when the incident and reflected angles are 0° and 75° respectively. Experimental results are in accord with finite element simulations and theoretical analyses. This advance in the proposed AM may pave a way for realizing more complex functionalities such as focusing, self-bending, and vortex generation.